Information literacy 2.0 - Banek Zorica, Mihaela (2009)
In the last decade the way knowledge is organized and made available has been radically altered. Users are witnessing the emergence of the new services, tools and technologies known as Web 2.0 environment. The significant attributes and features of these new tools relate to knowledge creation, management, sharing and dissemination causing the appearance of anomalies in the information literacy paradigm. Fact is that many of the aspects of current information literacy practices originate from a print-based culture which is incongruent with the transient and hybrid nature of digital environments. The authors examine the grounds for the possible re-conceptualizations in the field of information literacy and identify the current developments in the information universe.